2007
DOI: 10.1111/j.1365-3156.2007.01860.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of an antigen and antibody detection enzyme‐linked immunosorbent assay for cysticercosis as tools in an epidemiological study of epilepsy in Burundi

Abstract: Summaryobjective To evaluate the benefits of the detection of both circulating antibodies (Ab) and antigens (Ag) for the diagnosis of cysticercosis in people with epilepsy. Neurocysticercosis is a cause of neurological diseases world-wide, especially epilepsy. The clinical symptoms of neurocysticercosis are non-specific and diagnosis is often difficult.methods Serum samples were collected from subjects in a matched case-control study for epilepsy in the Kiremba area, Burundi, between March and April 2001 (epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Results for the same survey were found in several publications: It is the case for the survey of Nsengiyumva et al. (2003) whose data were completed in Prado‐Jean et al. (2007).…”
Section: Resultsmentioning
confidence: 52%
“…Results for the same survey were found in several publications: It is the case for the survey of Nsengiyumva et al. (2003) whose data were completed in Prado‐Jean et al. (2007).…”
Section: Resultsmentioning
confidence: 52%
“…The Ag-ELISA is reported to have a sensitivity of 94.4% and a specificity of 97.6% (Erhart et al, 2002;Prado-Jean et al, 2007) whilst the EITB has a sensitivity of 98% and a specificity of 100% according to Tsang et al (1989). However, since serological tests are not the gold standard for detecting cysticercosis, this overall seropositivity might be overestimated by the detection of transient antibodies (Garcia et al, 2001) or underestimated because of the presence of false negatives.…”
Section: Discussionmentioning
confidence: 97%
“…Since the geographical distribution of T. solium remains to be fully elucidated in most African countries, the risk of adverse effects could be significantly underestimated. Several studies in Africa have confirmed the presence of human cysticercosis and specifically NCC in areas where schistosomiasis is endemic [36, 3841]. Although NCC is considered more common in adults [42], children are also infected and in South Africa children down to the age of three have been found to suffer from NCC [43].…”
Section: Discussionmentioning
confidence: 99%